2017
DOI: 10.1007/s00592-017-1042-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal thickness as a marker of disease progression in longitudinal observation of patients with Wolfram syndrome

Abstract: AimsWolfram syndrome (WFS) is a recessively inherited monogenic form of diabetes coexisting with optic atrophy and neurodegenerative disorders with no currently recognized markers of disease progression. The aim of the study was to evaluate retinal parameters by using optical coherence tomography (OCT) in WFS patients after 2 years of follow-up and analysis of the parameters in relation to visual acuity.MethodsOCT parameters and visual acuity were measured in 12 WFS patients and 31 individuals with type 1 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…In order to confirm our observations and the fact that corneal changes in this case might depend on the gene and not the species, we carried out experimental tests on a mouse model [ 7 ]. Similarly, in our previous studies, we have documented that progressive retinal thinning is present among patients with Wolfram syndrome [ 2 ]. Thus, the number of mice we evaluated in the current study was low because the design of our project has only a confirmatory not an exploratory approach.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…In order to confirm our observations and the fact that corneal changes in this case might depend on the gene and not the species, we carried out experimental tests on a mouse model [ 7 ]. Similarly, in our previous studies, we have documented that progressive retinal thinning is present among patients with Wolfram syndrome [ 2 ]. Thus, the number of mice we evaluated in the current study was low because the design of our project has only a confirmatory not an exploratory approach.…”
Section: Methodssupporting
confidence: 75%
“…We have previously described that the average retinal thickness in WFS patients decreases with the progression of the disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zmysloska et al reported recently also decline of RNFL in patients with WFS followed on average 22 months. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Expression of miRNAs in patients with WFS and their changes over time were analyzed in relation to the results of simultaneous optical coherence tomography (OCT) and MRI tests of central nervous system, which are routinely performed in these patients in order to assess the progression of the disease, as described in detail previously. 12 21 …”
Section: Methodsmentioning
confidence: 99%